A Laboratory Investigation of the Reduction of the Iron Carbonate Bearing Ore to Iron Nugget by Means of the ITmk3 Ironmaking Technology - N. V. . Panishev (The Minerals, Metals and Materials Society, 2010)
The Bakal (South Ural, Russia) deposit of iron ore bearing iron carbonate (siderite) with the capacity of more than 1 billion tones belongs to the MMK. This ore cannot be fully processed via blast furnace technology because of high content of MgO. According to the investigations carried out in the USA and Japan in 1999-2004 the ITmk3 (Ironmaking Technology mark three) RHF technology is a breakthrough in Ironmaking. Four iron ore types (hematite, magnetite, high and low Al2O3/SiO2) were tested. Reduction, melting and slag removal can be achieved in just 10 min. The main objective of the investigation is to establish optimum operation conditions for the production of iron nuggets from iron carbonate bearing ore via the ITmk3 by means of the lab scale testing. Samples of iron ore and carbon reductant were chemically and physically analyzed. Green pellets were processed via a lab tube furnace to simulate RHF conditions. The nuggets and slag were chemically analyzed. This preliminary test work provides valuable information which may be used for large-scale testing in a commercially sized RHF.